Associations between multiple green space measures and birth weight across two US cities. (September 2017) - Cusack, Leanne; Larkin, Andrew; Carozza, Susan E.; Hystad, Perry
Abstract: Introduction: Several measures of green space exposure have been used in epidemiological research, but their relevance to health, and representation of exposure pathways, remains unclear. Here we examine the relationships between multiple urban green space metrics and associations with term birth weight across two diverse US cities. Methods: We used Vital Statistics data to create a birth cohort from 2005 to 2009 in the cities of Portland, Oregon (n = 90, 265) and Austin, Texas (n = 88, 807). These cities have similar green space levels but very different population and contextual characteristics. Green space metrics derived from mother's full residential address using multiple buffer distances (50–1000 m) included: Landsat Normalized Difference Vegetation Index (NDVI), % tree cover, % green space, % street tree buffering, and access to parks (using US EPA EnviroAtlas Data). Correlation between green space metrics were assessed and mixed models were used to determine associations with term birth weight, controlling for a comprehensive set of individual and neighborhood factors. City-specific models were run to determine how contextual and population differences affected green space associations with birth weight. Results: We observed moderate to high degrees of correlation between different green space metrics (except park access), with similar patterns between cities. Unadjusted associations demonstrated consistent protective effects of NDVI, % green space, % tree cover, and % street tree buffering for most buffer sizes on birth weight; however, in fully adjusted models most metrics were no longer statistically significant and no clear patterns remained. For example, in Austin the difference in birth weight for the highest versus lowest quartile of % green space within 50 m was 38.3 g (95% CI: 30.4, 46.1) in unadjusted and −1.5 g (98% CI: −8.8, 6.3) in adjusted models compared to 55.7 g (95%CI: 47.9, −63.6) and 12.9 g (95% CI: 4.4, 21.4) in Portland. Maternal race, ethnicity and education had the largest impact on reducing green space and birth weight associations. However, consistent positive associations were observed for the high density areas of both cities using several green space metrics at small buffer distances. Conclusions: This study highlights the importance of understanding the individual and contextual factors that may confound and/or modify green space and birth weight associations. Highlights: Moderate to high correlation exists between different green space metrics across two US cities. Positive associations existed between green space metrics and birth weight in unadjusted models. Adjustment for maternal race/ethnicity and education removed most green space associations. Positive associations between green space and birth weight remained in high density areas. Further knowledge of individual/contextual factors that may confound or modify green space is needed.